(p-ClPhSe)2 stimulates carbohydrate metabolism and reverses the metabolic alterations induced by high fructose load in rats. (September 2017) - Quines, Caroline B.; Rosa, Suzan G.; Chagas, Pietro M.; Velasquez, Daniela; Prado, Vinicius C.; Nogueira, Cristina W.
Abstract: The modern life leads to excess consumption of food rich in fructose; however, the long-term changes in carbohydrate and lipid metabolism could lead to metabolic dysfunction in humans. The present study evaluated the in vitro insulin-mimetic action of p -chloro-diphenyl diselenide ( p -ClPhSe)2 . The second aim of this study was to investigate if ( p -ClPhSe)2 reverses metabolic dysfunction induced by fructose load in Wistar rats. The insulin-mimetic action of ( p -ClPhSe)2  at concentrations of 50 and 100 μM was determined in slices of rat skeletal muscle. ( p -ClPhSe)2  at a concentration of 50 μM stimulated the glucose uptake by 40% in skeletal muscle. A dose-response curve revealed that ( p -ClPhSe)2  at a dose of 25 mg/kg reduced (∼20%) glycemia in rats treated with fructose (5 g/kg, i.g.). The administration of fructose impaired the liver homeostasis and ( p -ClPhSe)2 (25 mg/kg) protected against the increase (∼25%) in the G-6-Pase and isocitrate dehydrogenase activities and reduced the triglyceride content (∼25%) in the liver. ( p -ClPhSe)2 regulated the liver homeostasis by stimulating hexokinase activity (∼27%), regulating the TCA cycle activity (increased the ATP and citrate synthase activity (∼15%)) and increasing the glycogen levels (∼67%). In conclusion, ( p -ClPhSe)2 stimulated carbohydrate metabolism and reversed metabolic dysfunction in rats fed with fructose. Highlights: ( p -ClPhSe)2 had an insulin-mimetic action in vitro. ( p -ClPhSe)2 reduced glycemia increase in fructose-fed rats. ( p -ClPhSe)2 stimulates carbohydrate metabolism in fructose-fed rats. ( p -ClPhSe)2 restored the hepatic metabolic homeostasis in fructose-fed rats.